Anti-inflammatory properties of novel galloyl glucosides isolated from the Australian tropical plant Uromyrtus metrosideros. (1st December 2022) - Ritmejerytė, Edita; Ryan, Rachael Y.M.; Byatt, Brendan J.; Peck, Yoshimi; Yeshi, Karma; Daly, Norelle L.; Zhao, Guangzu; Crayn, Darren; Loukas, Alex; Pyne, Stephen G.; Ruscher, Roland; Wangchuk, Phurpa
Abstract: Two new galloyl glucosides, galloyl-lawsoniaside A (4 ) and uromyrtoside (6 ), were isolated from the polar fraction of Uromyrtus metrosideros leaf extract along with another four previously identified phytochemicals (1, 2, 3, and 5 ). The structures of these six compounds were characterised using low and high-resolution mass spectrometry (L/HRMS) and 1D and 2D Nuclear Magnetic Resonance (NMR) spectroscopy. These compounds were not toxic to human peripheral blood mononuclear cells (PBMCs) at 10 μg/mL over 24 h, yet showed significant in vitro suppression of proinflammatory cytokines involved in the pathogenesis of inflammatory bowel disease (IBD). Specifically, the release of interferon γ (IFN-γ), interleukin (IL)-17A, and IL-8 from phorbol myristate acetate/ionomycin (P/I) and anti-CD3/anti-CD28-activated cells were significantly suppressed by compounds 4 and 5 . Interestingly, no effect on tumour necrosis factor (TNF) release was observed. These results show that the newly characterised compound 4 has promising cytokine suppressive properties, which could be further investigated as a candidate for IBD treatment. Graphical abstract: Image 1 Highlights: Isolated six compounds in total from Uromyrtus metrosideros. Discovered two new galloyl glucosides-galloyl-lawsoniaside A and uromyrtoside. These compounds were not toxic to human peripheral blood mononuclear cells. Galloyl-lawsoniaside A and ( 4S )-α-terpineol 8- O -β-D-(6- O -galloyl)glucopyranoside showed significant anti-inflammatory activities.